Assesment of water quality of Sarani sangavi dam of Beed district (M.S.) India. - Patil, P V; Gaike, P P; Ningule, K B (International Multidisciplinary Research Journal, 2012)
Sarani Sangvi is a large minor irrigation dam. Constructed on the river Gobati and located at Kaij. The kaij, Majalgaon, Dharur and allied villages are benefited for irrigation and pisciculture. The dam is located 750-55’ latitude and 180-48’ longitudinal on Beed –Latur highway, covers 177 sq.km.ha.area,11Km away from Kaij Taluka .The river originates from Balaghat mountains and acts as best source of water for irrigation. The details of water quality assessment has discussed in text.